EXPLORING SUFISTIC VALUES IN THE CONTEXT OF ADAT BASANDI SYARAK: A STUDY OF IBN TAYMIYYAH'S SUFISM AND ITS RELEVANCE TO SOUTHEAST ASIAN ISLAMIC TRADITIONS - Hadi, Rahmad Tri; Samad, Duski; Gazali, Gazali; Ahmad (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2024)
This study explores Sufistic values within the Minangkabau philosophy of “Adat Basandi Syarak, Syarak Basandi Kitabullah” (ABS-SBK) through the lens of Ibn Taymiyyah’s Sufism. Known for his critiques of excessive mysticism, Ibn Taymiyyah also advocates a balanced Sufism that integrates devotion to God with social benefit. This research adapts his ideas to the Minangkabau context, emphasizing the compatibility between Islamic spirituality and local traditions. Using a descriptive-analytical method with an integrative approach, the study draws on Ibn Taymiyyah’s works as primary sources, supplemented by relevant secondary literature. The findings highlight key Sufistic elements in ABS-SBK, including self-purification, simplicity in living, the integration of spirituality with social responsibilities, critical engagement with bid‘ah, alignment of adat (custom) with syarak (Islamic law), and the pivotal roles of religious scholars (ulama) and cultural leaders (pemangku adat). Additionally, it identifies Sufistic dimensions in the cultural role of Bundo Kanduang in Minangkabau society. This study offers a novel perspective by bridging Ibn Taymiyyah’s moderate Sufism with Minangkabau’s local wisdom, providing a model for harmonizing Islamic principles with indigenous traditions. Its implications extend to broader discussions on contextualizing Islamic spirituality within diverse cultural settings.